Investigation of Theoretical Exams in Medical Faculties in Terms of Differential Item Functioning: Sample of Mersin University Medical Faculty - Huseyin Selvi; Ibrahim Bashan; Gonul Aslan (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Purpose: Current study investigated whether the measurement tools utilized during medical faculty preclinical period to form the basis of pass-fail decisions taken for students included Differential Item Functioning for foreign and Turkish students. Material and Methods: A total of 205 first year students 7 of which were foreign nationals attending Mersin University Medical Faculty participated in the study. All analyses are performed by Easy-DIF software and Mantel Haenszel method. And Differential Item Functioning identified this 6 items presented to the 10 expert for expert opinion Results: It was observed as a result of analyses via the method of Mantel Haenszel based on 7 exams that contained 100 multiple choice items each that only 6 items out of 700 included significant levels of Differential Item Functioning. It was also seen that item averages of foreign national students for the rest of all 694 items were lower compared to other students; however this difference was not statistically significant. Conclusion: According to the expert opinion for 6 items; long sentence structure, negative item root structure and some words that regarded as traditional play a role in the formation of Differential Item Functioning was found. It can be offered that we must not use long sentence structure, negative item root structure and some words that regarded as traditional for preparing exams to ensure validity of exams. [Cukurova Med J 2014; 39(2.000): 240-247]